Analysis of Determinants of Stock Transaction Volume and its Effect on the IDX Composite in IDX 2010-2020 Period - Salim, M. Noor; Siregar, Junira (Dinasti Publisher, 2022)
This study analyzes the impact of cash supply, dollar exchange rate, yuan exchange rate, Shanghai composite index (SSE composite index) on the IDX composite with transaction volume as a mediating variable (Case Study on Companies Listed on the Indonesia Stock Exchange in 2010 - 2020). The review was led utilizing 121 examples comprising of month to month information for all factors from 2010 to 2020. The information handling strategy utilized various straight relapse investigation procedures. The outcomes showed that to some extent cash supply, dollar exchange rate, SSE composite index had a critical constructive outcome on the IDX composite. To some degree, just the yuan exchange rate has no huge impact on the IDX composite. At the same time, cash supply, dollar exchange rate, yuan exchange rate and the SSE composite index simultaneously affected the IDX composite. The cash supply and the SSE composite index record have a critical constructive outcome on transaction volume. To some extent, exchange rate and yuan exchange rate have no critical impact on transaction volume. The cash supply, exchange rate, yuan exchange rate and SSE composite index simultaneously significantly affect on transaction volume. Simultaneously, cash supply, exchange rate, yuan exchange rate and SSE composite index significantly affect the IDX composite with exchange volume as an interceding variable.